URGENSI ADVOKASI MAHASISWA TERHADAP KEBIJAKAN PUBLIK DALAM PERSPEKTIF DAKWAH ISLAM - Wahyu Khoiruz Zaman (ASIAN PUBLISHER, 2022)
The background of this research is student advocacy in defending the weak, over the inequality of policies issued by the government. The purpose of this research is to understand the importance of advocacy by students on public policy. This research uses a library research approach. The method used is descriptive qualitative. The data collection technique uses literature review. While the data analysis technique uses data reduction to draw a conclusion. The results of this study indicate that advocacy by students for a policy issued by the government is quite important, especially when the policy issued is not pro-society. However, what must be considered in the delivery of advocacy carried out by students, must be based on the principles of Islamic da'wah. Thus, the advocacy delivered by students will be as expected and remain benefit-oriented.